MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS SISWA MATERI PEMBELAHAN SEL MENGGUNAKAN DISCOVERY LEARNING BERBASIS LKS DIVERGEN DI SMAN 14 SURABAYA - Hanifah, Alif (Inovasi: Jurnal Diklat Keagamaan, 2018)
Action Research This class aims to improve students’ criticalthinking on cell division material through Discovery Learningmodel based on Divergen LKS. The study was conducted 2 cyclesin October 2017. Data in the form of teacher action, studentlearning outcomes in the form of cognitive ability and criticalthinking skills of students. Indicator of the success of studentlearning increasing the value of learning outcomes with studentcompleteness of 95 %The result of research shows that the implementation ofDiscovery Learning model based on LKS di verging on thesubject of cell division carried out according to the learningstep and teacher guidance, can improve student learning resultthat is cognitive ability and critical thinking skill of studentsexperience improvement after learning, that is average of 70study result in cycle I and 82 in cycle 2. Classical completeness52,5 % after cycle I and 95 % after cycle II. Increased criticalthinking of students by 0.78 high category